Morinda officinalis oligosaccharides mitigate chronic mild stress-induced inflammation and depression-like behaviour by deactivating the MyD88/PI3K pathway via E2F2 - Zhu, Zhen-Hua; Yin, Xu-Yuan; Xu, Tu-Sun; Tao, Wei-Wei; Yao, Guang-Da; Wang, Pei-Jie; Qi, Qi; Jia, Qiu-Fang; Wang, Jing; Zhu, Yue; Hui, Li (Frontiers in Pharmacology, 2022)
Morinda officinalis oligosaccharides (MOs) are natural herbal extracts that have been shown to exert antidepressant effects. However, the mechanism of this effect remains unclear. Here, we explored the mechanism by which MOs improved experimental depression. Using a chronic mild stress (CMS) murine model, we examined whether MOs could protect against depressive-like behaviour. Lipopolysaccharide (LPS)- and ATP-treated BV2 cells were used to examine the potential mechanism by which MOs mediate the inflammatory response. We found that MOs prevented the CMS-induced reduction in the sucrose preference ratio in the sucrose preference test (SPT) and shortened the immobility durations in both the tail suspension test (TST) and forced swim test (FST). We also noticed that MOs suppressed inflammatory effects by deactivating the MyD88/PI3K pathway via E2F2 in CMS mice or LPS- and ATP-stimulated BV2 cells. Furthermore, overexpression of E2F2 blunted the beneficial effects of MOs in vitro. Collectively, these data showed that MOs exerted antidepressant effects in CMS mice by targeting E2F2-mediated MyD88/PI3K signalling pathway.